2007
DOI: 10.1207/s1532799xssr1101_2
|View full text |Cite
|
Sign up to set email alerts
|

Components of Reading Ability: Multivariate Evidence for a Convergent Skills Model of Reading Development

Abstract: Elementary and middle school children were given a large battery of tests evaluating reading subskills and reading-related cognitive abilities. These measures were used to define latent constructs representing skills and abilities believed to be important components of reading comprehension. Hypothesized relationships among these constructs were specified within the context of a structural model we call the "Convergent Skills Model of Reading Development," and developmental differences in the relative contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
164
0
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(188 citation statements)
references
References 34 publications
(39 reference statements)
9
164
0
15
Order By: Relevance
“…The convergent skills model (Vellutino et al, 2007) hypothesizes that language comprehension and the semantic and syntactic skills that underlie language comprehension are more strongly related to reading comprehension in older, more advanced readers. This is based on the assumption that language processes do not become fully operative until the child is able to identify the printed versions of the vast majority of the words they are able to comprehend in spoken language.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The convergent skills model (Vellutino et al, 2007) hypothesizes that language comprehension and the semantic and syntactic skills that underlie language comprehension are more strongly related to reading comprehension in older, more advanced readers. This is based on the assumption that language processes do not become fully operative until the child is able to identify the printed versions of the vast majority of the words they are able to comprehend in spoken language.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the SVR, word recognition skills and components of linguistic comprehension (vocabulary and grammar) have been found to be significant predictors of reading comprehension in typically developing children (e.g., Catts, Adlof, Hogan & Weismer, 2005, Kendeou, Savage & van Den Broek, 2009Muter, Hulme, Snowling, Stevenson, 2004). According to the convergent skills model proposed by Vellutino et al (2007) the relative contribution of word reading and language skills to reading comprehension are not stable across development; word reading is the best predictor of reading comprehension in the early stages of reading development, while language skills become the dominant predictor once accurate word identification has been achieved.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The first set of skills, called prerequisite skills, includes all of the skills needed to understand print, including oral reading fluency, word recognition, and decoding. Although some of these skills (e.g., decoding) are not typically addressed on high-stakes assessments, recent research has confirmed that providing feedback about students' mastery of prerequisite skills can help to move learning forward since deficiencies in critical prerequisite skills can compromise a 4 reader's ability to efficiently apply needed higher-order skills (Perfetti, 1985;Vellutino, Tunmer, & Jaccard, 2007).…”
Section: The Cbal Reading Competency Modelmentioning
confidence: 99%
“…The first set of skills, called prerequisite skills, includes all of the skills needed to understand print, including oral reading fluency, word recognition, and decoding. Although some of these skills (e.g., decoding) are not typically addressed on high-stakes assessments, recent research has confirmed that providing feedback about students' mastery of prerequisite skills can help to move learning forward since deficiencies in critical prerequisite skills can compromise a 4 reader's ability to efficiently apply needed higher-order skills (Perfetti, 1985;Vellutino, Tunmer, & Jaccard, 2007).The second skill set is called model building skills to emphasize its role in helping readers develop coherent mental representations of the information presented in stimulus materials. This second group includes all of the skills needed to form a coherent mental representation of a text, that is, its gist, including: (a) comprehending the literal meaning of individual sentences, (b) inferring the meaning of unfamiliar words, (c) using text-based inferences to infer cross-sentence links, (d) generating global inferences when required information is, or is not, highly activated in the text, and (d) using a text's network of hierarchical and logical relationships (i.e., its structure) to develop a more complete mental model of text content (Kintsch, 1998).…”
mentioning
confidence: 99%